Prediksi Kebutuhan Peralatan Gudang Menggunakan Triple Exponential Smoothing dalam Sistem Inventaris Berbasis Android - Pratiwi, Radila; Triase (Institut Teknologi Garut, 2025)
Spare parts inventory management at PT Wilco Tera Citra is still hampered by manual recording and fluctuations in demand. This study aims to develop an Android-based spare parts demand forecasting system using the Triple Exponential Smoothing (TES) method to support more measurable procurement decisions. The data consists of historical demand for 15 items over 12 months (2024). TES was applied to analyze the level, trend, and seasonal components, as well as to evaluate the sensitivity of the parameters a = 0.2, B = 0.2, y = 0.2. The results show low MAPE for Cylinder Liners (3.74%) and Fuel Injectors (4.60%), and moderate MAPE for Turbochargers (13.21%), with respective demand patterns: stable, seasonal, and declining trend. This study emphasizes methodological contributions through inter-item performance evaluation, TES integration into mobile inventory systems, and prediction support in procurement decision-making. Limitations include a relatively short 12-month dataset and an application that is not yet integrated with real-time stock data.